Novel: The Best Representation of Life - Sharma Kandel, Bhanu Bhakta (Janapriya Journal of Interdisciplinary Studies, 2020)
The debate, whether literature (art) can represent reality and life well has not been concluded, coming to no universal validity, since the time of Plato. The critics and the connoisseurs of art vary in their arguments for and against, some argue that literature represents reality and life and others deny it. They value and judge literature according to their own taste and subjective impression, it is claimed not only to be realistic but also fantastic, the frenzy of human imagination. Despite all the assertions against it, most of the literary critics have accepted that literature is a representation of life, though Plato has expelled the poets from his well run republic. Modern criticism of English literature takes its major impetus from Henry James for he is the first critic who speaks about representation of reality and life in literature, in novel. He has given prominent status to novel with an argument that it represents life better and more faithfully than any other genre of literature. For the discussion of the representation of realty in literature, Henry James’ Art of Fiction has been taken into account and MLA VIII has been used for citing the works.